Pengelolaan Persampahan Dalam Mendukung Perolehan Adipura di Kota Semarang - Pandie, Adrianus (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The ADIPURA award is one of Indonesian governmentâ€™s programs to encourage local governments towards ecological, social and economic sustainability, while maintaining the principals of good governance. Urban waste management as one of its evaluation components has the highest importance in its assessment; this aspect then became the focus of many local governments in their efforts to achieve the ADIPURA award. In 2010-2011 Semarang City has failed to achieve the award, however, it has succeeded to achieve it in the 2011-2012 period, among others due improvements in its urban waste management. The study employs positivistic rationalistic approach and examines four aspects of urban waste management policy implementation in Semarang city, including: acceptance, understanding, involvement and action, in supporting the efforts to achieve the ADIPURA award. Analysis are focused on the two periods of ADIPURA award in 2010-2011 and 2011-2012. AnalysisÂ found improvements in the four aspects of urban waste management during the period, which was indicated to have resulted in the success of achieving the award.